Future Asia the new gold rush in the East - Biswas, Rajiv (Palgrave Macmillan, 2013)
With traditional growth engines failing, the world is looking to Asia for economic salvation. This book charts the rise of China, India and ASEAN nations, who are increasingly being seen as the new growth drivers for the world, and discusses the imminence of a new global economic order.